1999
DOI: 10.1046/j.1365-2923.1999.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending community involvement in the medical curriculum: lessons from a case study

Abstract: Involving teachers and organizations which have not traditionally contributed to medical education raises philosophical issues around the aims and rationale of their involvement and practical issues such as gaining curriculum time, recruiting suitable teachers and gaining credibility for the courses. We analyse the benefits and difficulties inherent in broadening the curriculum in this way and assess the lessons our experience provides for the future expansion of such learning, both locally and nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Seabrook et al [14] found that a community-based program was beneficial for both community organizations and schools. Members of community organizations were able to obtain information regarding the university curriculum, and schoolteachers had the opportunity to learn about current medical issues and their application in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Seabrook et al [14] found that a community-based program was beneficial for both community organizations and schools. Members of community organizations were able to obtain information regarding the university curriculum, and schoolteachers had the opportunity to learn about current medical issues and their application in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further discussion or research is needed to verify the validity of the program. Seabrook et al reported that a community-based program was beneficial for both community organizations and schools; members of community organizations can obtain information regarding the university education curriculum, and school teachers have opportunities to learn about the latest medical issues and their applications in the community 13) . It was reported by Meyer et al that community-academic partnerships could contribute to the overall health of the community 14) , and Calleson et al reported that the balance between community needs and university requirements for knowledge was important 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, community staff were impressed, and the classes managed by students were judged to have had a good overall effect. It was reported that such a community-based programs are beneficial for both community organizations and schools; members of community organizations can obtain information regarding the university education curriculum, and in the meantime, teachers have opportunities to learn about the latest medical issues and their applications in the community 12) . Moreover, it was reported that community-academic partnerships could contribute to the overall health of the community 13) , and that the balance between community needs and university requirements for knowledge was important 14) .…”
Section: Discussionmentioning
confidence: 99%